Improving Community Health Outcomes through Integrated Services at Dewi Sartika Posyandu - Perkasa, Brama Syukri; Fajri, Imam Khoirul; Wandhana, Nana (Review of Primary Care Practice and Education, 2024)
Background: Posyandu Dewi Sartika plays a vital role in delivering integrated primary healthcare services (ILP) to the community. However, challenges such as low community participation, inadequate training for health cadres, and limited infrastructure hinder its effectiveness.Methods A community diagnosis approach was employed, integrating qualitative and quantitative methods. Data were collected through focus group discussions, observations, and document reviews. Challenges were identified and prioritized using the USG (Urgency, Seriousness, Growth) method, while solutions were developed and evaluated using the McNamara screening technique.Results: The study identified 12 key challenges, including low community participation, limited service coverage, inadequate documentation systems, and high resource demands. Priority issues were low community participation and insufficient cadre training, both scoring highest on the USG scale. Proposed solutions include innovative cadre training, the "Sehat Bersama Warga" community engagement program, and strengthened stakeholder collaboration to address these issues effectively. Conclusions: This study underscores the importance of participatory approaches, capacity-building initiatives, and cross-sector partnerships in addressing systemic challenges in integrated primary healthcare. The proposed solutions are scalable and have the potential to improve health outcomes and community engagement sustainably.